Environmental controls on storm intensity and charge structure in multiple regions of the continental United States. Issue 13 (7th July 2015) - Fuchs, Brody R.; Rutledge, Steven A.; Bruning, Eric C.; Pierce, Jeffrey R.; Kodros, John K.; Lang, Timothy J.; MacGorman, Donald R.; Krehbiel, Paul R.; Rison, William
Abstract A database consisting of approximately 4000 storm observations has been objectively analyzed to determine environmental characteristics that produce high radar reflectivities above the freezing level, large total lightning flash rates on the order of 10 flashes per minute, and anomalous vertical charge structures (most notably, dominant midlevel positive charge). The storm database is drawn from four regions of the United States featuring distinct environments, each with coinciding Lightning Mapping Array (LMA) network data. LMAs are able to infer total lightning flash rates using flash clustering algorithms, such as the one implemented in this study. Results show that anomalous charge structures inferred from LMA data, significant lightning flash rates, and increased radar reflectivities above the freezing level tend to be associated with environments that have high cloud base heights (approximately 3 km above ground level) and large atmospheric instability, quantified by normalized convective available potential energy (NCAPE) near 0.2 m s−2. Additionally, we infer that aerosols may affect storm intensity. Maximum flash rates were observed in storms with attributed aerosol concentrations near 1000 cm−3, while total flash rates decrease when aerosol concentrations exceed 1500 cm−3, consistent with previous studies. However, this effect is more pronounced in regions where the NCAPE and cloud base height are low. The dearth of storms with estimated aerosol concentrations less than 700 cm−3 (approximately 1% of total sample) does not provide a complete depiction of aerosol invigoration.